O Mercurio Peruano (1791-1795): ilustração em Lima, sentimento criollo e conhecimento útil - Cunha, Sharley José da (2021)
This study addresses the journal called Mercurio Peruano, which was designed and edited by a group of intellectuals – most of them criollos from the Sociedad Académica de Amantes del País – and distributed in colonial Lima between 1791 and 1795. To carry out an analysis of discursive and epistemological constructions in the several statements regarding the conception of geography, economy and natural history present in the documents, this study used the presumption that the type of Enlightenment produced by the intellectual editors of the journal aimed to what should be useful for the development of Peru. This study also presents the implications of the Bourbons’ Reforms in the Viceroyalty of Peru during the 18th century and how the editors of Mercurio reflected on these transformations. Finally, a brief history of Peruvian press in the second part of the 18th century is carried out, according to a point of view that stresses that this type of written production and its consequent dissemination among several criollo readers collaborated to create a patriotic group, with a growing and specific conception of peruanidad in Lima. The several statements present in the journal collaborated for the emergence of a discourse and a patriotic sentiment that is part of the history of the Criollismo in Americas